Prevention of Preharvest Sprouting through Hormone Engineering and Germination Recovery by Chemical Biology - Nonogaki, Mariko; Nonogaki, Hiroyuki (Frontiers in Plant Science, 2017)
Vivipary, germination of seeds on the maternal plant, is observed in nature and provides ecological advantages in certain wild species, such as mangroves. However, precocious seed germination in agricultural species, such as preharvest sprouting (PHS) in cereals, is a serious issue for food security. PHS reduces grain quality and causes economical losses to farmers. PHS can be prevented by translating the basic knowledge of hormone biology in seeds into technologies. Biosynthesis of abscisic acid (ABA), which is an essential hormone for seed dormancy, can be engineered to enhance dormancy and prevent PHS. Enhancing nine-cis-epoxycarotenoid dioxygenase (NCED), a rate-limiting enzyme of ABA biosynthesis, through a chemically induced gene expression system, has successfully been used to suppress germination of Arabidopsis seeds. The more advanced system NCED positive-feedback system, which amplifies ABA biosynthesis in a seed-specific manner without chemical induction, has also been developed. The proofs of concept established in the model species are now ready to be applied to crops. A potential problem is recovery of germination from hyperdormant crop grains. Hyperdormancy induced by the NCED systems can be reversed by inducing counteracting genes, such as NCED RNA interference or gibberellin (GA) biosynthesis genes. Alternatively, seed sensitivity to ABA can be modified to rescue germination using the knowledge of chemical biology. ABA antagonists, which were developed recently, have great potential to recover germination from the hyperdormant seeds. Combination of the dormancy-imposing and -releasing approaches will establish a comprehensive technology for PHS prevention and germination recovery.